Developing and validating a GT-suite based model for a second generation commonrail solenoid injector - Nguyen, Dat X; Nguyen, Vu H; Pham, Phuong X (Vietnam Journal of Science and Technology, 2021)
Injection profiles, containing important parameters like injection rate, directly affect the spray structure, fuel-air mixture quality, and as such the physical and chemical processes occurring in the IC engine’s combustion chamber. Therefore, injection profiles are one of the keys to improving power, thermal efficiency and minimizing the emission for IC engines. In this paper, a GT-Suite - based simulation model for a second generation solenoid commonrail injector typically utilized in Hyundai 2.5 TCI-A diesel engines, has been successfully developed and validated. The validation is done by using experimental data are acquired by a Zeuch’s method-based Injection Analyzer (UniPg STS) in University of Perugia, Italy. The calibration data is measured over a wide range of rail pressure and energizing time (ET) corresponding to the engine operating conditions. The results show that the injector model developed here is reliable and suitable for examining the injector’s hydraulic characteristics. The difference in start of injection values obtained through experiment and simulation is only about 15 µs. The total injection volumes obtained through experiment and simulation under ET > 0.8 ms is less than     10 % while the difference is quite high under ET < 0.8 ms and high rail pressure (up to 34.5 %).